Plasma dynamics in accelerator with plasma opening switch - Druj, O.S.; Yegorenkov, V.V.; Onyshchenko, I.M.; Yuferov, V.B. (Вопросы атомной науки и техники, 2019)
Plasma propagation in the pulse electron accelerator chamber with a plasma opening switch is investigated. Output beam and X-ray radiation parameters are shown to vary depending on the plasma channel location at the moment of current breaking. Experiments showing plasma compression into channels during the conductive phase of the plasma opening switch operation have been performed.